Penerapan Metode Pencatatan Perpetual Pada Sistem Informasi Kasir Penjualan dan Pencatatan Barang - Fikri Syah Putra Muchtar; Ucuk Darusalam (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
OTA shoe store is a shoe shop that sells local Indonesian shoes. But this shoe shop still carries out a sales system that is still very simple and inefficient, including transaction processing, recording shoe stock, and in making sales reports. This is the author's reference in designing a sales information system at the OTA Shoe Store. This system is designed using Sublime Text software with HTML, CSS, and PHP as the programming language, while for the database it uses MySQL. The design of this system is assisted by the Waterfall design method. The purpose or intent of this research is to design a cashier information system that can assist cashiers in processing transactions and can provide information to cashiers about the stock of shoes available in the warehouse. This information system can also help cashiers as admins in recording stock of goods based on the perpetual method of recording goods and can also make sales reports to be given to shop owners.